Effects of free maternity care on beneficiary satisfaction: Multicentre study conducted in the Binza Météo Health Zone, Kinshasa, Democratic Republic of the Congo - KAFUMBI, Joel; Mumvudi, M. F.; Lufwa, M. N.; Mabakutuvangilanga, N. S. D. (Orapuh Journal, 2025)
IntroductionThe Democratic Republic of Congo (DRC) ranks among the nations with the highest maternal mortality rates in the world, with 846 deaths per 100,000 live births.PurposeThis study aimed to assess the effects of free maternal health care on access, service quality, and beneficiary satisfaction, while also examining the socio-economic and psychological impact of this policy on women in the field of maternal health.MethodsThe survey employed a phenomenological qualitative approach to data collection and utilised the Donabedian model in the Binza Météo health zone. Data were collected through semi-structured interviews with 43 women who had given birth in selected maternity units. A thematic approach was used to analyse the interview content.ResultsThe results show that access to care improved with the elimination of financial barriers. Women expressed overall satisfaction with free antenatal consultations and childbirth. However, many difficulties remain, including indirect costs (e.g., transportation, drugs, and ultrasound scans), overloaded infrastructure and healthcare staff, and challenges related to hygiene and resource availability. Participants also emphasised the importance of healthcare staff's commitment, despite a few reported cases of negligence.ConclusionFree maternity care in the DRC has positively impacted both access and satisfaction; however, significant structural improvements are still required, particularly regarding funding, infrastructure, and medical staff working conditions.